Relation of size and sex to the natural diet of red crab Charybdis feriatus Linnaeus (Brachyura Portunidae) from Pilar-Capiz Bays, Northern Panay - Alabia, Irene D. (2003.)
A total of 395 (males=282; females=113) specimens of the red crab Charybdis feriatus were collected from Pilar-Capiz Bays from January-December 2002 and were used for the present study. Relative fullness index were computed for both sexes of different size classes. Results showed that stomachs of females were slightly fuller than that of males. Similar observation was made between juvenile and adult specimens. A total of 75 (males=57; females=18) gut contents were analyzed in detail. major food items in the diet of the crab include unidentified matter, unidentified eggs, fish crab, and shrimp remains. Frequency of occurence and combined visual estimation of unidentified organic matter were used for the examination. No dietary difference due to ontogenetic change were observed in the species while diet of male crabs were found to be more varied than those of females. However, frequency of occurence of major food items in the stomachs of both sexes was comparable.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Cahrybdis feriatus; Red crab